First evidence for direct CP violation in beauty to charmonium decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
The 𝐶⁢𝑃 asymmetry and branching fraction of the Cabibbo-Kobayashi-Maskawa-suppressed decay 𝐵+ →𝐽/𝜓⁢𝜋+ are precisely measured relative to the favored decay 𝐵+ →𝐽/𝜓⁢𝐾+ using a sample of proton-proton collision data corresponding to an integrated luminosity of 5.4 fb−1 recorded at a center-of-mass energy of 13 TeV during 2016-2018. The results of the 𝐶⁢𝑃 asymmetry difference and branching fraction ratio are Δ⁢𝒜𝐶⁢𝑃≡𝒜𝐶⁢𝑃⁡(𝐵+→𝐽/𝜓⁢𝜋+)−𝒜𝐶⁢𝑃⁡(𝐵+→𝐽/𝜓⁢𝐾+)=(1.29±0.49±0.08)×10−2, ℛ𝜋/𝐾≡[ℬ⁡(𝐵+→𝐽/𝜓⁢𝜋+)/ℬ⁡(𝐵+→𝐽/𝜓⁢𝐾+)]=(3.852±0.022±0.018)×10−2, where the first uncertainties are statistical and the second are systematic. A combination with previous LHCb results based on data collected at 7 and 8 TeV in 2011 and 2012 yields Δ⁢𝒜𝐶⁢𝑃 =(1.42 ±0.43 ±0.08) ×10−2 and ℛ𝜋/𝐾 =(3.846 ±0.018 ±0.018) ×10−2. The combined Δ⁢𝒜𝐶⁢𝑃 value deviates from zero by 3.2 standard deviations, providing the first evidence for direct 𝐶⁢𝑃 violation in the amplitudes of beauty decays to charmonium final states.